Viscoelastic description of electron subsystem of a semi-bounded metal within generalized "jellium" model - Kostrobij, P.P.; Markovych, B.M.; Vasylenko, A.I.; Tokarchuk, M.V. (Condensed Matter Physics, 2011)
Viscoelastic description of the electron subsystem of a semi-bounded metal on the basis of the generalized "jellium" model using the method of nonequilibrium statistical Zubarev operator is proposed. The nonequilibrium statistical operator and the quasi-equilibrium partition function calculated by means of the functional integration method are obtained. Transport equations for nonequilibrium mean values of electron density and momentum are received in the Gaussian approximation and in the following higher approximation that corresponds to the third-order cumulant averages in calculation of the quasi-equilibrium partition function. Запропоновано в’язко-еластичний опис електронної пiдсистеми напiвобмеженого металу на основi узагальненої моделi “желе” iз застосуванням методу нерiвноважного статистичного оператора Зубарєва. Отримано нерiвноважний статистичний оператор та вiдповiднi узагальненi рiвняння переносу для нерiвноважних середнiх значень операторiв густин числа електронiв та їх iмпульсу у гауcовому та вищому за ним наближенi, що вiдповiдає кумулянтним середнiм третього порядку при
розрахунку квазiрiвноважної статистичної суми методом функцiонального iнтегрування.